Analysis of factors affecting the occurrence of anemia in adolescent pregnancy: - Ainun Harahap, Mina; Ismah, Zata (Poltekkes Kemenkes Yogyakarta, 2024)
Anemia is a widespread global health problem and affects 56 million women worldwide, and two-thirds of them are in Asia, one of which is Indonesia. Based on Riskesdas 2018, anemia among pregnant women aged 15-24 years was 84.6%. This study aimed to determine the risk factors for anemia in pregnancy among adolescents. This study used a cross-sectional design. The location of this research is in Negeri Lama Public Health Center (PHC) in Negeri Lama Seberang, Bilih Hilir District, Labuhanbatu Regency, North Sumatra Province. The sample size was 120 samples using the formula difference between two proportions as sample size formula. The results showed that there was a significant relationship between compliance with iron and folic acid (IFA) consumption (P=0.000; PR:2.442), compliance with antenatal care (ANC) visits (P=0.028; PR:1.565), mental health status (P=0.00; PR:1.408). Based on the results of this study, it is known that the risk factors that are related to the incidence of anemia are compliance with IFA consumption, ANC visits, and mental health status.